Impact of Green Fodder Replacement with Corn Silage on Performance and Metabolizability in Growing Hariana Cattle - Verma, Ashwani Kumar; Kumar, Muneendra; Kumar, Vinod; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash; Shukla, Pankaj Kumar (Indian Journal of Animal Nutrition, 2021)
This study was conducted to determine the effect of green fodder replacement with corn silage on feed intake, growth performance and feed utilization efficiency in growing Hariana cattle. Corn silage was prepared in bunker silo and after ensiling for 60 days, silage was evaluated for nutrients content and physical and chemical characteristics. Low pH value, ammonia-nitrogen (NH3-N) and butyric acid content and high lactic acid, individual volatile fatty acids (VFAs), total VFAs content and buffering capacity (BC) denoted that prepared corn silage was well preserved and of very good quality. To study the effect of green fodder replacement with corn silage on animal performance, 18 growing Hariana heifers were randomly allocated into three groups (n=6) on body weight (130Â±3.0 kg) and age basis (14Â±1.5 months). Experimental heifers either received a basal total mixed ration (TMR) devoid of corn silage (S0%) or were fed on TMR of which 50% (S50%) and 100% (S100%) green fodder were replaced (DM basis) with corn silage. As the level of inclusion of corn silage increased, dry matter intake (DMI) also increased significantly (P